Strategi Pemasaran Jasa Pendidikan dalam Meningkatkan Minat Masyarakat Masuk Sekolah Dasar Islam Terpadu - Evi Zulfiah; Nita Novia Nugraha Putri; Muinah Fadhilah (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
The aim of this research is to look for marketing strategies, marketing implementation and both supporting and inhibiting factors in order to increase people's interest in entering SDIT Luqman Al Hakim Timoho. The method used is descriptive qualitative, data collection techniques using interviews, observation and documentation. Data analysis in this study is a qualitative analysis consisting of data reduction, presentation and conclusions. The validity of the data using triangulation, namely matching interview data, observation and documentation. The results of educational services marketing strategy in order to increase community interest, namely by collaborating between foundations and local teachers and community members, both in the areas of curriculum management, student management, infrastructure management, financial management, school and community relations management and service management special. The marketing implementation implemented is conducting market segments, determining target markets, and carrying out market positions, as well as marketing output. Supporting factors: schools have educators who teach according to their fields which make users of educational services more confident that SDIT Luqman Hakim has ways marketing that is different from other competitors in its class, and the entire academic community, parents, committees and partner institutions, both government and private, support the system from the foundation. Inhibiting factors, namely the level of concern from human resources has not been maximized in developing existing potential, the network is not yet wide, there is still a lack of program concepts, program escorts have not been maximized, the facilities and infrastructure have not been complete, there are still people who do not trust private schools, there is still a lack of interest in students in longer learning hours.